Engaging with Refuge or Refusal to Assess the Impact of an Immigration History Exhibition - Adina Langer (Journal of Community Engagement and Scholarship)
Public historians work in their communities to bridge the past and the present and help people make sense of the world in which they find themselves so that they can make better decisions about actions that will affect their future. This article assesses the impact of Refuge or Refusal, a museum exhibition created in 2018 to teach the public about U.S. immigration history. Building on findings about communicating history to the American public reported by the American Association for State and Local History, this article establishes the value of museum-based public history for sparking conversations, raising questions, and initiating a search for answers. After engaging with Refuge or Refusal, community members were empowered to think critically about the future they would inevitably help to create.